Research Trends and Knowledge Gaps in Pharmaceutical Lean Warehousing: A Bibliometric Analysis - Zulfa Maula; Agus Setiawan; Wiku Larutama (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
The pharmaceutical industry faces highly complex warehouse operations due to stringent regulatory requirements, product quality standards, and supply chain efficiency demands. Lean warehousing has been widely adopted to eliminate waste and improve warehouse operational performance. However, the growing body of research in this field has not been accompanied by a comprehensive scientific mapping, resulting in limited understanding of research trends and knowledge gaps. This study aims to map publication trends, intellectual structures, and research gaps in lean warehousing within pharmaceutical supply chains. A bibliometric approach was employed using Scopus-indexed articles published between 2015 and 2025, selected through the PRISMA protocol. A total of 34 articles were analyzed using VOSviewer through network, overlay, and density visualizations. The results indicate that this field remains an emerging research area characterized by three major thematic clusters: pharmaceutical warehouse operations management, pharmaceutical service quality management, and information system-based lean implementation. Research gaps were identified in key performance indicators, warehouse information systems, and warehouse resource optimization, which present promising directions for future studies.